Is Internet Reciprocal Teaching the Remedy for Saudi EFL Learners’ Reading Difficulties During the Covid-19 Pandemic? - Alasmari, Nasser (Journal of Education and e-Learning Research, 2021)
The aim of this study was to investigate the applicability of Internet Reciprocal Teaching (IRT) for remedial English reading instruction in the EFL context, specifically for the purpose of overcoming the reading difficulties encountered by low-achieving Saudi students majoring in English at the University of Jeddah. The treatment phase lasted three months and, due to the COVID-19 pandemic and the resulting shift to online teaching, the instruments used were an online pre- and post-test of reading comprehension, an IRT dialogue rubric downloaded on the Blackboard platform that is used for online teaching, as well as a phone interview conducted with randomly selected students from the sample. The findings indicated significant improvements in the reading comprehension of the Saudi learners participating this study, as reflected in the students’ effective use of the different IRT strategies and the significant results of the post-test. However, despite the proved effectiveness of IRT in strengthening reading comprehension, some challenges were voiced by the participants. These include computer competency, familiarity with online courses and, most notably, their linguistic difficulties with English, which justified their resorting to their native language (Arabic) as one way of demonstrating their comprehension. Finally, the paper draws pedagogical implications from the research results.